2011
DOI: 10.1063/1.3554480
|View full text |Cite
|
Sign up to set email alerts
|

Transport in graphene tunnel junctions

Abstract: We present a technique to fabricate tunnel junctions between graphene and Al and Cu, with a Si back gate, as well as a simple theory of tunneling between a metal and graphene. We map the differential conductance of our junctions versus probe and back gate voltage, and observe fluctuations in the conductance that are directly related to the graphene density of states. The conventional strong-suppression of the conductance at the graphene Dirac point can not be clearly demonstrated, but a more robust signature o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…In a technique referred to as gate-mapping tunneling spectroscopy [30,31], the differential conductance (dI/dV) was recorded as a function of tunneling sample bias, b , and gate voltage, For the present work we employ a mapping method [32], referred to as gate-averaged spectroscopy, where we calculate the average of all spectra that were recorded over our full gate These excitations are better discerned in IETS, where they appear as point symmetric peaks ћ and dips ћ with respect to zero bias. The latter identifies them as inelastic excitations.…”
mentioning
confidence: 99%
“…In a technique referred to as gate-mapping tunneling spectroscopy [30,31], the differential conductance (dI/dV) was recorded as a function of tunneling sample bias, b , and gate voltage, For the present work we employ a mapping method [32], referred to as gate-averaged spectroscopy, where we calculate the average of all spectra that were recorded over our full gate These excitations are better discerned in IETS, where they appear as point symmetric peaks ћ and dips ћ with respect to zero bias. The latter identifies them as inelastic excitations.…”
mentioning
confidence: 99%
“…Since metals will eventually be involved in some way in graphene circuits, as interconnects or gates, it is critical to understand their effect on the graphene. Theoretical 3,4 and experimental [5][6][7][8][9][10] publications have found that one of the major effects of a metal on graphene is doping. In addition to this, it is believed that some metals interact weakly, leaving the linear dispersion of graphene undisturbed, and thus it may be desirable to use such metals near regions where graphene properties are most important.…”
mentioning
confidence: 99%
“…These are resonances in the DOS caused by the disorder potential, and the slope dV g /dV p becomes slightly flatter at positive gate voltage, where the density of states is lower. This we interpret as a broadened Dirac point, 9 and its location at positive gate voltage means the graphene is hole doped. As the magnetic field is increased, these lines are seen to break up, and are replaced by lines with a staircase like structure of alternating high and low sloped lines.…”
mentioning
confidence: 99%
See 2 more Smart Citations